2014
DOI: 10.1016/j.fob.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The levels of RAC3 expression are up regulated by TNF in the inflammatory response

Abstract: HighlightsThe inflammatory response increases the expression of RAC3 in vitro and in vivo.TNF induces the increase of RAC3 at transcriptional level through NF-κB activation.Glucocorticoids also induce the increase of RAC3 expression levels.RAC3 appears to be essential for NF-κB- and GR-mediated transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…RAC3 is a known high expression molecule in several types of tumors including colorectal cancer [ 29 ]. However, it was not clearly determined at present if this overexpression could be early detected at tumor initiation and then homogeneously sustained along the cancer progression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RAC3 is a known high expression molecule in several types of tumors including colorectal cancer [ 29 ]. However, it was not clearly determined at present if this overexpression could be early detected at tumor initiation and then homogeneously sustained along the cancer progression.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, inflammation is increasingly recognized as a critical component in tumor initiation and progression [ 41 , 42 ]. Furthermore, we have previously demonstrated that inflammatory cytokines as TNF may upregulate the RAC3 gene expression [ 29 ]. Therefore, in this context, the induction of malignant or premalignant lesions from cells acquiring this RAC3 overexpression and possible additional mutations or epygenomic rearrangements sounds as a possible source for tumor initiating cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corepressor silencing mediator for retinoid and thyroid hormone receptors (SMRT) preferentially interacts with the antagonist-bound PRA, and the coactivators steroid receptor coactivator 1 (SRC-1) and 2 (SRC-2) have a higher affinity for PRB. 9 Less information is available regarding SRC-3 (AIB1), an oncogene associated with endocrine resistance [10][11][12][13] and PR action in the mammary gland. 14 Antiprogestins inhibit breast cancer growth in several experimental models [reviewed in Ref.…”
mentioning
confidence: 99%
“…With the MR model it has been shown that the whole undissociated complex is detectable in the nucleus for several minutes after translocation (Galigniana et al 2010b; Grossmann et al 2012). One other protein that can be associated with the nuclear translocation complex is RAC3 (receptor-associated co-activator 3), a protein that exerts an anti-apoptotic activity by activating NF-kappaB, AKT and p38 MAPK and by inhibition of caspase 9, AIF (apoptosis-inducing factor) and ERK2 (extracellular signal regulated kinase 3/MAPK6) (Colo et al 2008; Alvarado et al 2014). …”
Section: Inductors Of Hsp90(ab1)mentioning
confidence: 99%